Case report: Atomoxetine improves chronic pain with comorbid post-traumatic stress disorder and attention deficit hyperactivity disorder - Kasahara, Satoshi; Takahashi, Miwako; Morita, Taito; Matsudaira, Ko; Sato, Naoko; Momose, Toshimitsu; Niwa, Shin-Ichi; Uchida, Kanji (Frontiers in Psychiatry, 2023)
Background It is known that patients reporting chronic pain often experience trauma or post-traumatic stress disorder (PTSD) and tend to be more difficult to treat. Attention deficit hyperactivity disorder (ADHD), a neurodevelopmental disorder, is frequently associated with chronic pain. Furthermore, patients diagnosed with ADHD are more likely to encounter trauma and develop PTSD because of their inattentive and impulsive tendencies. There are reports stating that atomoxetine (ATX), a selective noradrenaline reuptake inhibitor for ADHD, is effective in patients diagnosed with PTSD and ADHD. However, there have been no reports on cases of comorbid PTSD and ADHD with chronic pain, and ATX’s potential in improving chronic pain coexisting PTSD. Furthermore, no reports have evaluated patient cerebral blood flow in conjunction with the course of treatment with ATX for chronic pain. Case report In this study, we reported a case where ATX improved chronic pain with PTSD and improved cerebral blood flow. The patient was a 56-year-old woman exhibiting chronic pain with PTSD, resulting from 6 years of severe domestic violence from her common-law husband. She had no history of ADHD diagnosis, but through aggressive screening, comorbid ADHD was diagnosed. When treated with ATX, there were significant improvements in her pain, quality of life, anxiety, depression, catastrophic thoughts, and cerebral blood flow. As a result, she could resume work after 11 years. Conclusion The study showed that chronic pain with PTSD may be comorbid with ADHD. Moreover, we found that ATX can improve chronic pain with PTSD and cerebral blood flow. Aggressive screening of ADHD is important because once the diagnosis of comorbidity is confirmed, an ideal ADHD treatment can be selected. Therefore, based on the results of this study, ATX may be a candidate for treatment for cases of chronic pain with PTSD and ADHD.